2021
DOI: 10.3310/hsdr09050
|View full text |Cite
|
Sign up to set email alerts
|

Non-pharmacological interventions to reduce restrictive practices in adult mental health inpatient settings: the COMPARE systematic mapping review

Abstract: Objectives The study aimed to provide a mapping review of non-pharmacological interventions to reduce restrictive practices in adult mental health inpatient settings; classify intervention components using the behaviour change technique taxonomy; explore evidence of behaviour change techniques and interventions; and identify the behaviour change techniques that show most effectiveness and those that require further testing. Background … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
50
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(68 citation statements)
references
References 196 publications
5
50
0
Order By: Relevance
“…Recent years have seen the development of interventions designed specifically to reduce conflict and use of restrictive practices in inpatient wards. A recent systematic review 82 identified two programmes with trial evidence of effectiveness, Safewards 83 and Six Core Strategies 84 , both of which now commonly inform practice 85 . These are multi‐component team‐level interventions, which target avoiding or mitigating potential flashpoint situations resulting from interactions between patients, staff‐patient interactions, or the ward regulatory or physical environment.…”
Section: Intensive Treatment Following Crisismentioning
confidence: 99%
“…Recent years have seen the development of interventions designed specifically to reduce conflict and use of restrictive practices in inpatient wards. A recent systematic review 82 identified two programmes with trial evidence of effectiveness, Safewards 83 and Six Core Strategies 84 , both of which now commonly inform practice 85 . These are multi‐component team‐level interventions, which target avoiding or mitigating potential flashpoint situations resulting from interactions between patients, staff‐patient interactions, or the ward regulatory or physical environment.…”
Section: Intensive Treatment Following Crisismentioning
confidence: 99%
“…However, coercive methods in care should not be used only because there is a lack of available alternative methods for seclusion and restraint. For example, in their systematic mapping review, Baker et al [ 34 ] found 105 interventions to reduce restrictive practices in adult psychiatric inpatient settings. Most of them were multicomponent interventions tested in non-randomized designs.…”
Section: Discussionmentioning
confidence: 99%
“…The aim of this step is to identify a body of literature that contains relevant data to further develop and test the initial programme theory developed from Step 1. The search strategy will be structured and guided by the initial programme theory, previous relevant reviews [ 10 , 33 , 46 , 47 ] and by consultation with the project stakeholder groups (i.e. research team, advisory panel, and experts by experience groups).…”
Section: Methodsmentioning
confidence: 99%